Islam as the driving force for humanity and world peace - Mhd. Sarif, Suhaimi (2016)
This keynote postulates Islam as the driving force for humanity and world peace in the contexts of contemporary world. Islam is the way of life as stated in the Qur’an and in the traditions of the Prophet Muhammad Peace be Upon Him. The essence of Islam denotes humanity with peace under the guidance of revelation and reasoning. The dual roles of human as servant and vicegerent of Allah for the true success in this world and in the Hereafter require human to maintain relationships with Allah, with fellow human beings and other creatures. The trust (amanah) upon human in the forms of duties (taklifiyyah) and leadership (masuliyyah) requires them to behave with justice (‘adl) and benevolence (ihsan). The indicators of humanity and world peace used by Global Peace Index are used as reasoning (aqli) evidence that the world is lack of humanity and less peaceful. An opinion survey with young Muslims (age between 20 and 24) argued that humanity and peace begin from individual then to family, community, state, and nation. They suggested a remedial action through self-transformation (islah) and collective approach (amal jamaie) on good deeds.